The impact of the movement control order phases on the quality of life among Malaysian university students / Maisarah Shari ... [et al.] - Shari, Maisarah; Raja Hussain, Raja Nurul Jannat; Abu Kasim, Nurul Ain; Ab Razak, Rozella; Mohamed Kassim, Nur Atikah; Md Japilus, Siti Jameelah (Universiti Teknologi MARA, 2023)
This study measured the impact of the different phases during movement control order on the quality of life among local Malaysian university students aged >18 years old. An online survey was distributed through a social media platform during the movement control order (MCO; 20 April to 12 May 2020) and conditional movement control order (CMCO; 12 to 20 May 2020). The same participants completed the SF-36 quality of life questionnaire that assessed the overall physical health, mental health, and eight domains which are physical functioning (PF), physical role functioning (RF), bodily pain (BP), general health perceptions (GH), vitality (V), social role functioning (SF), emotional role functioning (EF), and mental health (MH) in both phases. A total of 523 participants (Male = 222, female = 301) completed the survey. A Wilcoxon signed-rank test showed that there was a significant difference in participants' quality of life between the MCO and CMCO phases